Design and Implementation of PCV Device Based on Arduino Board - Baban, Huda Farooq Jameel; Yaseen, Suhiar Mohammed Hasan (Al-Nahrain Journal of Science, 2018)
There are many methods which can be used to determine packed red blood cells volume (PCV) value. Some of them are direct and another are indirect methods. However using of the manual ruler to evaluate PCV is the easiest and more economic method which is commonly used as a direct way to determine PCV but with probability of personal errors and plasma trapped. In our search, we have been designed and implemented electronic circuit which is depended on Arduino board to evaluate PCV. The new measuring device is consisted of red light (600nm) emitters or diodes to benefit of specified absorbance of this light by erythrocytes (red blood cells) in comparison with lowest absorbance of red light by blood plasma. Then, the transmitted light is received by photocell and photocell’s signal is processed by Arduino board. The difference of light intensity between incident and transmitted light after it passes through centrifuged blood sample makes PCV evaluation method reliable on. Seventeen diodes and photocells which are included in this device make determination process of erythrocytes volume to total blood volume easiest and more accurate. Finally using of programmable Arduino board 2560 mega (with determined mathematical equations which are stored in Arduino memory) to calculate and screen PCV and Hb (hemoglobin) values, it makes analysis of PCV blood reliable and simple treatment.